Human Capital Disclosure and Labor Market Outcomes: Evidence from Regulation S‐K - Choi, Jung Ho; Li, Dan; Macciocchi, Daniele (Journal of Accounting Research, 2026)
ABSTRACT We examine the labor market consequences of the 2020 Regulation S‐K requiring human capital disclosure in 10K filings. Using large‐sample job‐level data and a Generative Large Language Model (GLLM), we observe that public firms subject to the regulation increase their disclosure of diversity, equity, and inclusion (DEI) information in job postings relative to a matched sample of large private firms. The increase in job‐posting disclosure is more pronounced among firms facing greater external pressure to increase their workforce diversity. These findings suggest a shift in demand for diverse candidates by public firms following the regulation. Yet, consistent with short‐term inelastic labor supply, this demand shift lengthens the recruitment period, with noticeable increases in workplace gender diversity emerging one year after the regulation, particularly among firms that demonstrate a credible commitment to DEI. Our study documents how securities regulations can impact labor market practices and underscores the challenges involved in shaping workforce diversity.